The Wood(s): On the Problem of Living Matter in Ancient and Contemporary Biology - Bibikhin, Vladimir (Stasis, 2018)
The Wood(s) [Les] by Vladimir Bibikhin was originally published in Russian in 2011. This translation is published by arrangement with Publising House “Nauka”, SPb. Translated by Michael Marder.